Production costs and profitability in coriander fertilised with Calotropis procera under organic cultivation - Barros Júnior, Aurélio; Souza, Ênio; Ribeiro, Rayanne Maria; Martins, Bruno; Silveira, Lindomar (Revista Ciência Agronômica, 2019)
The present study was carried out to determine the amount of biomass of Calotropis procera and itsincorporation time into the soil that provide maximum productivity and profitability in the organic cultivation of coriander during the spring and autumn-winter, under the conditions of Serra Talhada, in the state of Pernambuco, Brazil. The experiment was conducted in a randomised complete block design, in a 4 x 4 factorial scheme with three replications. The first factor corresponded to the amount of biomass (5.4, 8.8, 12.2 and 15.6 t ha-1 on a dry basis), and the second to the incorporation time (0, 10, 20 and 30 days prior toplanting the coriander). In addition to the green-matter yield and production costs, the following economic indicators were determined: gross and net incomes, rate of return and profitability index. An amount of 12.2 t ha-1 C. procera in the spring and 8.8 t ha-1 in the autumn-winter resulted in greater productivity and profitability in coriander production. The incorporation of green manure 13 days (spring) and 23 days (autumn-winter) prior to sowing the crop was considered ideal for the economic viability of the activity. For the autumn-winter crop, the net income (BRL 19,607.10 ha-1) and rate of return (3.31) were respectively 58.6% and 28.8% higher than those obtained in the spring.